Pengaruh Media Busy Book Untuk Pengenalan Sex Education Pada Anak Usia Dini di TK Permata Bunda Teluk Leban - Nurul Ofifa; Uswatul Hasni; Sri Indriani Harianja (Yayasan Al-Afif, 2026)
This research is motivated by field observations that indicate that the introduction of sex education to children aged 5–6 years at Permata Bunda Kindergarten in Teluk Leban Village has not been running optimally. Children's knowledge regarding sex education is still relatively low, so some children do not understand the basic concepts of sex education. This condition has the potential to increase children's vulnerability, both as victims and perpetrators of violence and sexual deviation. Therefore, innovative efforts are needed in learning that can effectively improve children's understanding, one of which is through the use of interesting and interactive learning media. This study aims to determine and analyze the effect of the use of busy books on the introduction of sex education to early childhood at Permata Bunda Kindergarten in Teluk Leban. The type of research used is quantitative research with an experimental design using a pretest-posttest one group design. The sampling technique was carried out using purposive sampling, resulting in group B1 with 25 children as the research sample. Data collection was carried out through observation sheets, while data analysis included normality tests, homogeneity tests, and hypothesis testing using paired sample t-tests. The results showed that the use of busy books had a positive and significant influence on the introduction of sex education to early childhood. This is indicated by an increase in scores from the pretest stage of 452 with an average of 18.08 to 674 in the posttest stage with an average of 26.96. In addition, the results of the hypothesis test using a paired sample t-test showed a significance value of 0.000 (p < 0.05), which means there is a significant difference between before and after treatment. The paired sample correlation value of 0.87 indicates that the influence given is in the very strong category. Thus, it can be concluded that the use of busy book media has a significant effect in increasing the introduction of sex education to early childhood at Permata Bunda Kindergarten